Transport costs, trade, and geographic concentration: Evidence from Canada - Kristian Behrens; W. Mark Brown (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2017)
Our objective is threefold. First, we explain how to estimate transport costs and the geographic concentration of industries using trucking microdata and geocoded plant-level data. Second, we document that transport costs explain between 25% to 57% of the observed relationship between trade and distance across Canada's economic regions. Last, we show that changes in transport costs have a substantial impact on geographic concentration patterns for vertically linked industries, depending on the strength of the links. A one standard deviation increase in transport costs leads to a 0.02 standard deviation decrease in geographic concentration for industry pairs at the bottom decile of the input-output coefficient distribution, whereas the corresponding effect at the top decile is a 0.02 standard deviation increase. This gap between weakly and strongly linked industries stands up to a wide range of specifications and is robust to instrumental variables estimations.
Keywords: R12; C23; L60; 330; Transport costs; trade; geographic concentration; Canada